2018
DOI: 10.1051/matecconf/201814901062
|View full text |Cite
|
Sign up to set email alerts
|

Blended cement hydration assessment by thermogravimetric analysis and isothermal calorimetry

Abstract: In the present study, the hydration of Portland cement pastes containing 5%, 10%, 15% and 20% tuff, limestone filler and granodiorite was investigated by thermogravimetric analysis coupled with differential scanning calorimetry and microcalorimetry isotherm. The monitoring of the hydration kinetics by thermogravimetric analysis made it possible to quantify the quantity of water combined with the cement (nonevaporable water) and the degree of hydration. By coupling this technique to the differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The portlandite content reflects the degree of hydration of the cement, and secondary additions can also indicate the degree of pozzolanic activity. Lower levels of portlandite in admixed cement paste indicate lower hydration levels, as shown in other studies [2,14,15].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The portlandite content reflects the degree of hydration of the cement, and secondary additions can also indicate the degree of pozzolanic activity. Lower levels of portlandite in admixed cement paste indicate lower hydration levels, as shown in other studies [2,14,15].…”
Section: Introductionsupporting
confidence: 81%
“…Cement hydration is a sum of chemical processes that lead to the changes of anhydrous phases into different hydrated phases. These chemical transformations are accompanied by a set of physical processes that participate in the construction of the microstructure of the cement paste the process of hydration of cements combined by more or less reactive secondary additions is necessary and more complicated, Nevertheless, these mineral additions modify the treated hydration by physical and chemical means, often quite difficult to dissociate [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, TGA was conducted on cementitious composites after water curing and carbonation. The use of TGA has been well documented for the evaluation of cementitious composites dehydration. , The results showed that cement composites that contain 3% of biochar have higher mineral carbonization potential than composites without biochar by up to 7%–13%.…”
Section: Environmental Applications Of Biocharmentioning
confidence: 99%
“…It is usually calculated as the mass loss from an initial to a final temperature (WL Ti-Tf ), with some correction factor (CF). Different initial temperatures (T i ) are considered in the literature, for example, 50 • C after solvent exchange [55], 105 • C [47,[56][57][58][59][60][61], 110 • C [62] and 140 • C [63].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Other researchers correct the content of non-evaporable water by subtracting 59% of the difference between the mass loss relative to the decarbonation of the sample and the mass loss relative to the decarbonation of the anhydrous material (530-1100 • C) [59]. The same CF is used by [61], but with a narrower temperature range for the decarbonation (600-800 • C), whereas [60] use this same CF for samples with mineral additions, with three additional items: addition of the device's drift, subtraction of loss on ignition (LOI) of the cement (multiplied by the cement mass in the sample), and subtraction of the LOI of the addition (multiplied by the addition mass in the sample). In [63], the mass loss related to the decarbonation of the anhydrous material is subtracted, but no reduction coefficient is used.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%